POTENTIALS YIELD AND FISHERIES OF MALAHAYU RESERVOIR, BREBES - Setiya Triharyuni; Aisyah Aisyah; Chairulwan Umar; Husnah Husnah (Indonesian Fisheries Research Journal, 2019)
Fishing activity in Malahayu Reservoir has been done since long time. Unlimited fishing may impact to the decresing of fish resources of those waters. This study presents an assessment of fishing practices in Malahayu reservoir between 2008-2016 periods. Data of potential fish production and catch per unit effort were estimated by using different estimate models, catch per unit effort was analyzed annually, while potential fish production was analyzed by using five models namely model by Henderson & Welcome (1974), Teows & Griffith (1979), Marshal (1984), Moreau & De Silva (1991) and Crul (1992). The results show that changes of fish composition has accured, which was originally dominated by native fish while for now it is dominated by 72,05% of tilapia (Oreochromis niloticus) as an introduced fish. Furthermore, the average catch per unit effort (CPUE) in Malahayu reservoir is about 11,82 kg / fisherman, while the average potential production is about 198,55 kg / year. CPUE value and potential production indicate that exploitation rate in Malahayu Reservoir are in fully-exploited or perhaps over-exploited condition. Related to those conditions, not to increase the number of efforts (fishermen) as a management option towards sustainable fisheries.